Contextual factors in local energy policy choices: comparative case of solar energy policy in two cities - Curley, Cali; Aloise-Young, Patricia; Harrison, Nicky; Xu, Corey Kewei; Duggan, Gerald P.; Zimmerle, Daniel (Frontiers in Sustainable Energy Policy, 2023)
Numerous recent calls have been made for policy design research to embed itself throughout the policy process and explore avenues for matching tools and targets. These calls have argued that policy design research, while emphasizing the content and the choice of design, has been under-leveraged, particularly in exploring rationales for effectiveness. In this paper, we conduct a comparative case study to explore variation in participation rates for two similarly categorized solar policies across two mid-sized cities. In this regard, three contextual factors are examined, including the population characteristics, the existing configuration of policies, and the physical environment, which all contribute to shaping policy effectiveness. We argue that policy design is situated within an explicit context and that without capturing the context, the effectiveness of policies may not translate if diffused.